Environmental assisted cracking of aluminium alloy AA 6061 / Azman Anuar and Ashari Kasmin - Anuar, Azman; Kasmin, Ashari (2000)
Aluminium alloy 6061 is widely used as structure, components and equipment in seawater such as propellers, shafts, pumps, piping system and ship hulls. Since aluminium alloys AA 6061 have various type of application in corrosive environment (seawater) and easily available in market, we decide to do an environmental assisted cracking studies. This is to collect meaningful data and then to predict the effect of seawater to this type of alloy in term of mechanical properties such as ductility, yield strength, tensile strength, and percentage of elongation. One of the environmental assisted cracking testing which have been selected is stress corrosion cracking. The method that has been used in this stress corrosion cracking testing is a constant load condition. Specimens of aluminium alloy AA 6061 is conditioning under constant tension at 250N in seawater environment. The duration of the conditioning is varied from one test to another. For the purpose comparison, we also conditioned the specimen of aluminium alloy AA6061 in seawater without loading. The duration of this conditioning also varies from one to another. Both conditioning have had been carried out at room temperature.